2005
DOI: 10.1007/s00774-005-0649-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and turnover in patients with acromegaly in relation to sex, disease activity, and gonadal function

Abstract: Acromegaly is a rare disease caused by growth hormone (GH) hypersecretion. GH and insulin-like growth factor-I (IGF-I) exert anabolic activity in bones. Nevertheless, bone mineral density (BMD) loss is not uncommon in patients with acromegaly. It is assumed to be due to hypogonadism associated with the acromegaly. The aim of the study was to examine BMD at various skeletal sites and bone turnover and to assess the influence of impaired gonadal function and disease activity on BMD and turnover changes in acrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 22 publications
2
39
0
7
Order By: Relevance
“…The biochemical markers reflect bone resorption (CTX-1) and formation (P1NP) and together they describe bone turnover (11,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemical markers reflect bone resorption (CTX-1) and formation (P1NP) and together they describe bone turnover (11,27).…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling is coupled in as well active acromegaly as following treatment (11), in contrast to for instance endogenous Cushing's syndrome, where bone resorption and formation are uncoupled in the active state, becoming coupled following treatment and remission (36). It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the anabolic effects of GH on bone mineral density (BMD) may be sustained after cure of acromegaly (1)(2)(3)(4)(5), but duration of follow-up was relatively short in the majority of studies. The effects of GH excess on BMD appear to be less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In active acromegaly, high circulating concentrations of GH and IGF1 are associated with increased cortical BMD (6)(7)(8)(9)(10). The reported effects of GH/IGF1 excess on trabecular BMD are more variable, with studies reporting either increased or decreased BMD at trabecular sites possibly due to the variable presence of hypogonadism (1,(3)(4)(5)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Bone turnover is increased, suggesting activation of both osteoblasts and osteoclasts in active acromegaly (1)(2)(3)(4)(5)(6)(7). Moreover, biochemical markers of bone formation and bone resorption correlate with circulating GH and IGF-I levels suggesting that GH and liver-derived IGF-I may have direct effects on both cell types in modulating turnover (1,2,8,9).…”
Section: Introductionmentioning
confidence: 99%